The influence of financial risk on bank performance - Maelanal Husna; Amelya Rahma Maulida; Henny Setyo Lestari (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2025)
This study examines how financial risk affects the performance of banks listed on the Indonesia Stock Exchange (IDX). The research relies on secondary data sourced from the annual reports of IDX-listed banks for the 2020–2024 period. The sample comprises 36 banks, yielding 180 observations that meet the established criteria. To evaluate the proposed hypotheses, panel data analysis was conducted using E-Views 9. The independent variables include credit risk, liquidity risk, operational risk, bank size, GDP growth, and inflation. Conclusions were drawn based on the results of the panel regression model. The study finds that financial risk plays a role in shaping bank performance. Credit risk negatively impacts performance, whereas liquidity risk does not show a meaningful effect. Operational risk also negatively affects performance. Bank size, on the other hand, contributes positively to bank performance. GDP growth rate has a positive effect on banking performance, whereas inflation has no significant effect